Unusual Case of Low-Velocity Large Object Penetrating the Frontal Bone with Favorable Outcome: A Case Report in Pediatric Patient - Daulay, Elvita Rahmi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Penetrating head injury is one of the deadliest forms of head trauma; the outcome is usually low, and patients who survive long enough require complex medical treatment. Immediate imaging assessment with appropriate management can improve patient recovery. CASE REPORT: We reported a case of head penetration trauma on a 12-year-old child with embedded cylindrical iron that enters the skull without any signs of neurological deficit. CONCLUSIONS: This case shows that aggressive diagnostic imaging and emergency care followed by proper immediate head surgery management and postoperative intensive care to monitor and intervene in possible surgical and medical complications could significantly improve patient outcomes.